2004
DOI: 10.1590/s1415-54192004000600015
|View full text |Cite
|
Sign up to set email alerts
|

Caminhos e descaminhos da Ortodontia no Brasil

Abstract: Devido à constatação do aumento do número de ortodontistas e de Cursos de Ortodontia, delineou-se este estudo cujo objetivo foi sondar o futuro da especialidade. Avaliaram-se formulários respondidos por 413 alunos e 130 professores de 42 Cursos de Especialização dos 73 relacionados no Catálogo da Associação Brasileira de Ortodontia e Ortopedia Facial (ABOR) 1999/2000. Obteve-se uma taxa de resposta de 57,53%. A amostra foi dividida em: alunos e professores e nas regiões: Sul + Sudeste e Centro-Oeste + Nordeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…10 Comparing Brazil and the United States, a fact calls attention: despite of having a population equivalent to 40% of that in the United States and 82% less income, Brazil has almost three times more orthodontics courses (n=124, 2001). 10 The majority of practitioners revealed a pessimistic outlook in regard to the future of the specialty. The main reasons mentioned are: market saturation, unofficial courses, competition with general clinician and insufficient income.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Comparing Brazil and the United States, a fact calls attention: despite of having a population equivalent to 40% of that in the United States and 82% less income, Brazil has almost three times more orthodontics courses (n=124, 2001). 10 The majority of practitioners revealed a pessimistic outlook in regard to the future of the specialty. The main reasons mentioned are: market saturation, unofficial courses, competition with general clinician and insufficient income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main reasons mentioned are: market saturation, unofficial courses, competition with general clinician and insufficient income. 10 The review of literature showed the absence of more specific studies on the current status of the profession in specific regions in Brazil. In this context, interest has risen in creating a profile of these practitioners in the state of Minas Gerais in order to improve professional practice and achieve excellence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations